Ferri's clinical advisor 2016 - Ferri, Fred F. (Elsevier, 2015)
Ferri’s Clinical Advisor 2016 is simply the fastest, most effective way to access up-to-date diagnostic and treatment information on more than 700 common medical conditions. The popular "5 books in 1" format provides quick guidance on diseases and disorders, differential diagnoses, medical algorithms, laboratory tests, and clinical practice guidelines. Yearly updates by experts in key clinical fields ensure that you’re current with fast-changing medical knowledge, and extra electronic content delivers more than 100 exclusive topics, additional algorithms, and much more